TOWARDS AI-DRIVEN GEOSPATIAL EDUCATION: A CURRICULUM REFORM FRAMEWORK FOR GEOMATICS PROGRAMS IN TRANSITION ECONOMIES. - Andy Okereke, Chukwudi; Chukwuma Emeribeole, Augustine (African Journal of Social and Behavioural Sciences, 2026)
Geomatics Education in transition economies faces a dual challenge: maintaining foundational skills in Surveying and Mapping while integrating disruptive technologies such as artificial intelligence (AI), machine learning, and smart geospatial systems. As global industries increasingly rely on AI-driven geospatial intelligence for urban planning, environmental monitoring, disaster management, and sustainable development, geomatics programs must undergo curriculum reform to remain relevant and effective. This paper proposes a curriculum reform framework that embeds AI literacy, geospatial data science, and interdisciplinary collaboration into traditional geomatics education. The framework rests on three pillars: integrating AI tools and methods into core courses, encouraging partnerships between academia, industry, and government to ensure applied relevance, and cultivating ethical and critical thinking to address data governance and societal impacts. Utilizing a qualitative research design built upon the Context, Descriptor, and Coherence (CDC) curriculum development model and a thematic analysis of international initiatives, the framework demonstrates how transition economies can leapfrog developmental barriers and produce graduates capable of harnessing AI-driven geospatial systems for evidence- based decision-making. By situating geomatics education within the broader context of digital transformation, the study positions these programs as catalysts for innovation, resilience, and sustainable growth. Graduates trained under this model are prepared to meet the challenges of a rapidly evolving geospatial landscape while upholding ethical standards and contributing to socially inclusive, sustainable development.